Infectivity of Plasmodium berghei Sporozoites Delivered by Intravenous Inoculation versus Mosquito Bite: Implications for Sporozoite Vaccine Trials - Vaughan, Jefferson A. (American Society for Microbiology, 1999)
Plasmodium berghei sporozoites delivered by mosquito bite were more infectious to outbred CD-1 mice than were sporozoites delivered by intravenous inoculation. The route of challenge also affected vaccine efficacy. In view of these findings and the fact that mosquito bites are the natural mode of sporozoite delivery, infectious mosquito bites should be considered the challenge protocol of choice for sporozoite vaccine efficacy trials.